2007
DOI: 10.1038/sj.onc.1210664
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mammary tumors from Brg1 heterozygous mice

Abstract: Mammalian SWI/SNF-related complexes have been implicated in cancer based on some of the subunits physically interacting with retinoblastoma (RB) and other proteins involved in carcinogenesis. Additionally, several subunits are mutated or not expressed in tumor-derived cell lines. Strong evidence for a role in tumorigenesis in vivo, however, has been limited to SNF5 mutations that result primarily in malignant rhabdoid tumors (MRTs) in humans and MRTs as well as other sarcomas in mice. We previously generated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
127
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(134 citation statements)
references
References 16 publications
5
127
1
1
Order By: Relevance
“…This suggests a mechanism for the observed mitotic abnormalities, because disruption of such domains compromises mitotic fidelity. It has been recently reported that tumors arising in Brg1 ϩ/Ϫ mice, although not mimicking specific pathways, are best characterized by genomic instability (Bultman et al, 2008). Importantly, this study also concludes that tumor formation in Brg1 ϩ/Ϫ mice occurs due to haploinsufficiency rather than loss of heterozygosity (Bultman et al, 2008), suggesting a lack of selection or proliferative advantage with the complete ablation of Brg1.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This suggests a mechanism for the observed mitotic abnormalities, because disruption of such domains compromises mitotic fidelity. It has been recently reported that tumors arising in Brg1 ϩ/Ϫ mice, although not mimicking specific pathways, are best characterized by genomic instability (Bultman et al, 2008). Importantly, this study also concludes that tumor formation in Brg1 ϩ/Ϫ mice occurs due to haploinsufficiency rather than loss of heterozygosity (Bultman et al, 2008), suggesting a lack of selection or proliferative advantage with the complete ablation of Brg1.…”
Section: Discussionsupporting
confidence: 67%
“…It has been recently reported that tumors arising in Brg1 ϩ/Ϫ mice, although not mimicking specific pathways, are best characterized by genomic instability (Bultman et al, 2008). Importantly, this study also concludes that tumor formation in Brg1 ϩ/Ϫ mice occurs due to haploinsufficiency rather than loss of heterozygosity (Bultman et al, 2008), suggesting a lack of selection or proliferative advantage with the complete ablation of Brg1. Thus, in the context of Brg1 deficiency, resultant dispersion of pericentric heterochromatin domains and mitotic dysfunction could potentially represent the underlying key etiological feature relevant to tumorigenesis.…”
supporting
confidence: 67%
“…As cited above, the BAF47 knockout mouse is the most tumorigenic model reported to date . Knockout experiments with BRG1 and BRM have revealed that loss of either ATPase can potentiate cancer development in mice Bultman et al, 2000Bultman et al, , 2008Glaros et al, 2008). However, interpretation of the results of these experiments is complicated by the possibility that BRG1 and BRM can potentially compensate for each other in certain circumstances.…”
Section: Transgenic Knockout Of Brm or Brg1 Enhances Transformationmentioning
confidence: 99%
“…Knockout of a single allele of BRG1 results in spontaneous tumor development in about 10% of BRG1 þ /À mice within a year (Bultman et al, 2000(Bultman et al, , 2008. These tumors originated from the milk line and stained for histopathology markers indicative of mammary tumors.…”
Section: Transgenic Knockout Of Brm or Brg1 Enhances Transformationmentioning
confidence: 99%
“…Consistently, Brg1 heterozygous mice are predisposed to subcutaneous glandular tumors with histological features similar to breast adenocarcinomas (Bultman et al, 2000). High incidence of mammary tumors or lung cancers was also reported in the Brg1 mutant mice (Bultman et al, 2008;Glaros et al, 2008). Snf5 heterozygous mice are prone to tumors resembling malignant rhabdoid tumors (Klochendler-Yeivin et al, 2000;Roberts et al, 2000;Guidi et al, 2001).…”
Section: Introductionmentioning
confidence: 59%